DETERMINATION OF MAINTENANCE PRIORITY INDONESIAN NAVY SHIP DEPO LEVEL USING FUZZY MCDM - Donni Kartiko; Suparno Suparno; Okol S Suharyo; Ahmadi Ahmadi; Arica Dwi Susanto (JOURNAL ASRO, 2018)
The Indonesian Navy as a defense and security force of the sea has combat tools and supporting facilities projected in the Integrated Fleet Weapon System (Sistem Senjata Armada Terpadu/SSAT) with several components including Indonesian navy ships, marines, aircraft and bases. Depo level maintenance is comprehensive maintenance that can only be carried out by personnel who are experts in their field and supported by complete and sophisticated equipment and facilities. Maintenance at this level includes complete overhaul repairment, repowering MLM (mid life modernization), calibration of all equipment, and repairs to all parts thoroughly. Depo Level Maintenance is the nature of maintaining technical conditions based on rotary hours. If the repair schedule specified in the SPT (System for Planned Maintenance), the schedule must be carried out. This research aimed to present a priority setting solution in Depo level maintenance wherein the highest Indonesian Navy Ship ranking is determined from the level of the decision makers. Fuzzy MCDM is a method developed for decision making on several alternative decisions to get an accurate and optimal decision. In Indonesian Navy Ship Hardepo priority ranking process taken from the level of data processing decision makers using the Fuzzy MCDM method, the 5 highest priority values in implementation were obtained. Hardepo with the highest scores were KRP-812 0.111, BDU-841 0.108, LAM-374 0.107, KRS-624 0.097 and TJA-541 0.073